Factors Facilitating Virtual Organization Adoption In Malaysia - Mohd Ghazali, Shazli Mansor (2007)
This research investigates the factors facilitating for Virtual Organization adoption in Malaysia. The factors investigated in this study are Industry Type, Organization Culture and Infrastructure.